Schoenberg's twelve-tone music : symmetry and the musical idea - Boss, Jack Forrest (Music since 1900., 2014)
Jack Boss presents detailed analyses of Arnold Schoenberg''s twelve-tone pieces, bringing the composer''s ''musical idea'' - problem, elaboration, solution - to life.